Variability of the Festuca-dominated vegetation on calcareous rocks in the Muránska Planina Mts - Mucina, Ladislav; Valachovič, M. (2004)
Tussock grasslands dominated by Festuca pallens and Festuca tatrae are a striking feature of vegetation of calcareous rocky habitats (steep rocky slopes, cliffs) of the mountain ranges of the Western Carpathians. We have studied the plant communities formeded by the above-mentioned fescue species in the Muránska Planina Mts., and found out that the floristic difference between the respective communities built by F. pallens and F. tatrae appears to be less pronounced than for instance in the Nízke Tatry Mts. and Slovenský raj. Mts. In the Muránska Planina Mts. palaeo-endemic Daphne arbuscula and neo-endemic Pulsatilla subslavica were found in these communities. Another interesting feature is the frequent co-occurrence of both taxons of Festuca in the studied region.